Hadhonah Rights of Children (Not Mumayyis) Based on Compilation of Islamic Law and Child Protection Act - Muhammad Fitri Adi (Islamic Research Publiser, 2023)
Abstract: This study aimed to determine the Hadhonah Rights of Children who have not been Mumayiz to Biological Fathers According to the Compilation of Islamic Law (KHI) and Law No. 23 of 2002 Concerning Child Protection. This type of research is qualitative, which produces descriptive data from observations. This research is in the form of an analysis of cases relating to the Decision on hadhanah rights to biological fathers for children who have not mumayyiz according to Compilation of Islamic Law (KHI) and Law Number 23 of 2002, which occurred in the Religious Courts stab. An important finding in this research is the Judge's Consideration in deciding case Number: 1242/Pdt.G/2017/PA.Stb., which gives the hadhanah rights of children who have not been mumayyiz to biological fathers after a divorce, does not follow the provisions of the Compilation of Islamic Law articles 156 and 105, Law No. 1 of 1974 concerning marriage, and Law No. 23 of 2002 concerning child protection.